1989
DOI: 10.1002/mrd.1120220407
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and role of microfilaments during early events of sheep fertilization

Abstract: The distribution of actin was studied during early events of sheep fertilization by fluorescence microscopy after staining with 7-nitrobenz-2-oxal-1.3 diazole (NBD)-phallacidin and anti-actin antibody and by electron microscopy after heavy meromyosin labelling. unfertilized and fertilized eggs exhibited a continuous band of fluorescence with both NBD-phallacidin and anti-actin antibody. Unlike in mice, no high concentration of actin overlying the spindle was detected in ovulated sheep oocytes. At the site of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
23
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 28 publications
4
23
0
Order By: Relevance
“…The present results showed that the meiotic spindle of the porcine oocyte is peripherally located and radially oriented with its long axis as seen in other domestic species [6,8,10] and humans [16], and no rotation of the meiotic spindle occurred unlike in laboratory rodents [3,5]. Further, the meiotic spindle is barrel-shaped in the pig ( [11] and this study) and cattle [10], and is approximately 10 µm long, whereas in laboratory rodents it is much more elongated and tapered [5,23] with a length of 26.4 ± 0.3 µm in the mouse [23] and 16.4 ± 0.7 µm in the hamster (our unpublished observation).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The present results showed that the meiotic spindle of the porcine oocyte is peripherally located and radially oriented with its long axis as seen in other domestic species [6,8,10] and humans [16], and no rotation of the meiotic spindle occurred unlike in laboratory rodents [3,5]. Further, the meiotic spindle is barrel-shaped in the pig ( [11] and this study) and cattle [10], and is approximately 10 µm long, whereas in laboratory rodents it is much more elongated and tapered [5,23] with a length of 26.4 ± 0.3 µm in the mouse [23] and 16.4 ± 0.7 µm in the hamster (our unpublished observation).…”
Section: Discussionsupporting
confidence: 74%
“…During oocyte aging, peripheral microfilaments, which are involved in anchorage of the spindle to the oocyte cortex [8,[12][13][14][15]26], drastically reduced in density as observed here. Kim et al [11] observed that the meiotic plate was frequently located outside of the microfilament-rich domain in aged pig oocytes.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…(v) Remnants of sperm tails and midpieces were seen in the vicinity of centrioles at spindle poles. (vW) Furthermore, the presence of centrioles associated with the flagellar'neck piece of spermatozoa in pronuclear stage oocytes has also been reported in the human (25), pig, and sheep (26,27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, each cytoskeletal system (i.e., actin, microtubules, and intermediate filaments) has adapted specialized features to allow them to push through the developmental transition. For example, at fertilization, a loose actin-based network of filaments intimately associates with the head and neck of a sperm for normal, efficient sperm penetration; a specialized function for actin that occurs only once in the lifetime of an organism (Maro et al, 1985;Le Guen at al., 1989;Webster and McGaughey, 1990). Our data suggest that kaz also has adapted a specialized role during these early transitions.…”
Section: Fig 12 A-fmentioning
confidence: 99%